Pengaruh Pertumbuhan Laba Dan Likuiditas Terhadap Kualitas Laba Pada Perusahaan Sektor Industrial Dan Healthcare Yang Terdaftar Di BEI 2020-2022 - Kania Widiyastuti; Fauzan Akbar Albastiah (CV. ITTC INDONESIA, 2024)
Investor attention to the quality of a company's earnings is generally high, as they tend to prefer entities with high-quality earnings. The phenomenon of a continuous decline in profits will encourage management to engage in earnings manipulation. The purpose of this research is to determine the effect of profit growth and liquidity on earnings quality in companies in the industrial and healthcare sectors listed on the Indonesia Stock Exchange from 2020 to 2022. Using a quantitative research type with secondary data sources and the analysis method of multiple linear regression analysis, Purposive sampling refers to the selection of samples based on criteria set by the researcher. From a population of 96 companies, a sample of 32 companies was ultimately obtained, with a time series of 3 years, resulting in a total of 96. The results of the research from the t-test indicate that H0 is accepted, meaning that, partially, profit growth does not affect earnings quality. Meanwhile, for the liquidity research, H2 is accepted, indicating that, partially, liquidity has a negative impact on earnings quality. Additionally, the results from the F-test show that, simultaneously, profit growth and liquidity affect earnings quality.